Socioeconomic Adversity, Social Resources, and Allostatic Load among Hispanic/Latino Youth: The Study of Latino Youth - Gallo, Linda C. (Psychosom Med, 2019)
OBJECTIVE. We examined associations among socioeconomic adversity, social resources, and allostatic load in Hispanic/Latino youth, who are at high risk for obesity and related cardiometabolic risks. METHODS. Participants were N=1343 Hispanic/Latino youth (51% male; ages 8–16 years) offspring of Hispanic Community Health Study/Study of Latinos (HCHS/SOL) participants. Between 2012–2014, youth underwent a fasting blood draw and anthropometric assessment, and youth and their enrolled caregivers provided social and demographic information. A composite indicator of allostatic load represented dysregulation across general metabolism, cardiovascular, glucose metabolism, lipid, and inflammation/hemostatic systems. Socioeconomic adversity was a composite of caregiver education, employment status, economic hardship, family income relative to poverty, family structure, and receipt of food assistance. Social resources were a composite of family functioning, parental closeness, peer support, and parenting style variables. RESULTS. Multivariable regression models that adjusted for sociodemographic factors, design effects (strata and clustering), and sample weights revealed a significant, positive, association between socioeconomic adversity and allostatic load (β=.10, p = .035) and a significant, inverse association between socioeconomic adversity and social resources (β=−.10, p = .013). Social resources did not relate to allostatic load, and did not moderate or help explain the association of adversity with allostatic load (all ps > .05). CONCLUSIONS. Statistically significant, but small associations of socioeconomic adversity with both allostatic load and social resources were identified. The small effects may partially reflect range restriction given overall high socioeconomic adversity and high social resources in the cohort.